Об изменчивости морфо-физиологических особенностей популяции непарного шелкопряда (Porthelria dispar L.) в Нижнем Приднепровье - Киреева, И.М. (Вестник зоологии, 1975)
Investigation of the larva characters in Porthetria dispar L. from the Lower Dnieper population showed great variation and variability in colouration of the individuals. The character of the caterpillar colouration and ratio of the quantity of their separate colour groups are established to depend on the nutrition character of the individuals and phase of the population number dynamics.